2015
DOI: 10.4158/ep14295.cr
|View full text |Cite
|
Sign up to set email alerts
|

Diffuse Large B-Cell Lymphoma Presenting with Diabetes Insipidus: A Case Report

Abstract: Objective:To present a rare case of pituitary gland involvement in paranasal and central nervous system (CNS) lymphoma.Methods: We describe the clinical presentation, laboratory data at presentation and follow-up, imaging studies, and management of the patient. A brief review of literature regarding pituitary involvement in lymphoma is also presented.Results: A 53-year-old woman with a history of human immunodeficiency virus (HIV) infection was evaluated for 6-month history of polydipsia, high-volume polyuria,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…Kaur et al reported an HIV-PCNSL case with involvement of the hypothalamus, pituitary, and paranasal sinuses, marked by central diabetes insipidus. Multidrug chemotherapy with "EPOCH-R" (etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab) and intravenous methotrexate yielded neurological improvement after treatment (15). Bello et al presented a case of HIV-PCNSL with a space-occupying lesion extending into the suprasellar spaces, causing hypothalamic compression.…”
Section: Discussionmentioning
confidence: 99%
“…Kaur et al reported an HIV-PCNSL case with involvement of the hypothalamus, pituitary, and paranasal sinuses, marked by central diabetes insipidus. Multidrug chemotherapy with "EPOCH-R" (etoposide, prednisone, vincristine, cyclophosphamide, doxorubicin, and rituximab) and intravenous methotrexate yielded neurological improvement after treatment (15). Bello et al presented a case of HIV-PCNSL with a space-occupying lesion extending into the suprasellar spaces, causing hypothalamic compression.…”
Section: Discussionmentioning
confidence: 99%
“…The latter had a similar clinical presentation as the reported case regarding hypopituitarism and DI; however, our patient was younger (age, 29 vs 53 years) and had a worse virulogic control. In immunocompetent patients, the age of presentation also usually is more advanced, isolated diabetes insipidus is more common, tumor size is smaller and treatment response is more favorable ( 13 ). The case is noteworthy due to the atypical clinical presentation of a CNS lymphoma as diabetes insipidus.…”
Section: Discussionmentioning
confidence: 99%